A highly sensitive and selective molecularly imprinted sensor for direct determination of ultra‐trace Cr(III) in environmental samples. Issue 10 (14th March 2022) - Ling, Jun; Wei, Ge; Li, Jianping
Abstract: Aiming at the insufficient sensitivity and selectivity of the existing detection methods for trivalent chromium in environmental samples, an efficient strategy is proposed. In this study, the complex Cr(III)‐Oxine was used as the target molecule of the molecularly imprinted sensor. The ligand Oxine was used for the primary recognition of Cr(III), and the molecular imprinted cavities was used for the secondary recognition of Cr(III)‐Oxine, which greatly improved the selectivity of the sensor to Cr(III). At the same time, the high‐efficiency catalytic effect of Cr(III)‐Oxine on the Luminol‐H2 O2 system is used to promote the electrochemiluminescence (ECL) intensity, so as to achieve the improving the detection sensitivity of Cr(III). The established method based on the sensor can be used for the detection of Cr(III) in the concentration range of 5×10 −10 ∼5×10 −8 mol/L with a detection limit of 1.78×10 −10 mol/L. Abstract : A MIP‐ECL sensor was prepared for Cr(III) ion detection. High selectivity is due to the dual recognition effect, i. e., the recognition of Oxine to Cr (III) ion during the formation of the Cr(III)‐Oxine complex and the recognition of MIP to Cr(III)‐Oxine. High sensitivity is attributed to the catalytic amplification of the luminol‐H2 O2 system by Cr(III)‐Oxine, which results in an enhanced ECL signal.